JURIDICAL REVIEW OF THE LEGAL POSITION OF EMPLOYMENT RELATIONS WITHOUT A WRITTEN EMPLOYMENT AGREEMENTS - Anak Agung Sagung Ngurah Indradewi; Ni Luh Ade Krisnatalingsih (Warmadewa Press, 2021)
Work agreements made in oral form do not conflict with the provisions of Law Number 13 of 2003 concerning Employment, i.e. contained in the provisions Article 51 paragraph 1, i.e. employment agreements are made in writing or verbally. The research aims are to examine the legal position of the worker in the employment relationship without a written employment agreement and the legal protection of workers and workers against the fulfillment of workers' rights in employment without a written employment agreement. The type of research used in this study is normative legal research. The source of legal material came from primary and secondary legal material source. The legal position of employment relations without a written employment agreement based on the perspective of labor law has a strong, legal position as long as it does not conflict with the legal conditions of the employment agreement, as provided for in Article 52 paragraph (1) of Law Number 13 of 2003 concerning Employment. As a result of the law of employment without a written employment agreement, if the type of employment agreement is a Specific Time Work Agreement made in oral form, then the status changes to an Unspecified Time Work Agreement and if the type of employment agreement is an Unspecified Time Work Agreement then the employer is obliged to issue a letter of appointment to the worker/labor concerned to become a permanent worker. Verbal work agreements have not been able to provide full legal protection to workers, potentially harming workers and workers to the fulfillment of their rights and obligations as workers.